Penerapan Model Pembelajaran Students Team Achievement Division (STAD) dalam Meningkatkan Hasil Belajar Agama Hindu - Ida Bagus Gede Suyadnya (Jurnal Penjaminan Mutu, 2017)
The purpose of this research is to know the application of "Cooperative Type" learning model STAD (Student Team Achievement Division) in improving the result of learning Hindu Religion students.This research includes classroom action research (PTK) with cyclustic design In this research used research subjects 13 students, taken from the students of class VII A who have not met the criteria of mastery learning.The target of research is the result of learning Hindu Religion students in SMP Negeri 4 Negara.After the data collected, then analyzed with quantitative descriptive analysis.Results of data analysis showed an increase of average The results of Hinduism learning obtained on the pre cycle of student learning outcomes only reached 69.09 and in the first cycle student learning outcomes increased 77.39.And in Cycle II student learning outcomes rose to 83.48 Or from pre-cycle to cycle I increased by 12,01%, from pre cycle to cycle II equal to 20,83%, and cycle I to si Second cluster of 7.87%. Based on the results of this data analysis, it can be concluded that the implementation of Cooperative Type STAD learning model can improve the learning result of Hindu religion students in SMP Negeri 4 Negara, Jembrana District.